2009
DOI: 10.1097/qad.0b013e32832d3b85
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical atherosclerosis due to HIV infection: carotid intima-medial thickness measurements from the FRAM study

Abstract: Background Cardiovascular disease (CVD) is an increasing cause of morbidity and mortality in HIV-infected patients. However, it is controversial whether HIV infection contributes to accelerated atherosclerosis independent of traditional CVD risk factors. Methods Cross-sectional study of HIV-infected and control subjects without pre-existing CVD from the study of Fat Redistribution and Metabolic Change in HIV Infection (FRAM) and the Multi-Ethnic Study of Atherosclerosis (MESA). Pre-clinical atherosclerosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
247
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(267 citation statements)
references
References 41 publications
13
247
2
4
Order By: Relevance
“…Some studies have found a higher prevalence of subclinical atherosclerosis in HIVpositive patients [13][14][15] but the results are not consistent. Consequently we performed a systematic review to understand the prevalence and the peculiarities of coronary plaques in asymptomatic HIV-positive patients.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some studies have found a higher prevalence of subclinical atherosclerosis in HIVpositive patients [13][14][15] but the results are not consistent. Consequently we performed a systematic review to understand the prevalence and the peculiarities of coronary plaques in asymptomatic HIV-positive patients.…”
Section: Introductionmentioning
confidence: 83%
“…evaluated quality of included studies on pre-specified forms. Modifying the MOOSE items to take into account the specific features of included studies, [15][16][17][18] we separately abstracted and appraised study design, setting, data source, as well as risk of analytical, selection, adjudication, detection, and attrition bias (expressed as low, moderate, or high risk of bias, as well as incomplete reporting leading to inability to ascertain the underlying risk of bias). For the quality assessment of the selected studies we used the Newcastle-Ottawa Scale (NOS) for Assessing the Quality of Nonrandomized Studies in Meta-Analysis 19 .…”
Section: Internal Validity and Quality Appraisalmentioning
confidence: 99%
“…There is an interplay between infl ammation, HIV proteins, immune dysfunction, ART effect, malnutrition, and other factors in understanding the patophysiological basis of CVD among PLHIV. Studies using carotid intima-media thickness (CIMT) found that PLHIV asymptomatic had increased subclinical atherosclerosis [4,5]. Furthermore, study using coronary CT angiography (CCTA) confi rmed that PLHIV had increase coronary plaque even after controlling traditional CVD risk factors [6].…”
Section: Editorialmentioning
confidence: 99%
“…Zwischen 50 und 70 % der HIV-positiven Patienten hatten mindestens eine Komorbidität [65]. Hierbei ist besonders brisant, dass HIV-positive Patienten diese altersassoziierten, also "normalen" Alterserkrankungen zwischen 5 und 10 Jahre früher bekommen als eine alters-und geschlechtsgematchte Vergleichsgruppe aus der Allgemeinbevölkerung [66]. Auch wenn man Rauchen, Substanzgebrauch und andere "Life-style"-bedingte Risikofaktoren aus diesem Vergleich herausnimmt, haben HIV-positive Patienten ein deutlich erhöhtes Risiko früher einen Herzinfarkt oder Schlaganfall zu erleiden als ihre HIV-negativen Altersgenossen [66].…”
Section: Bedeutung Von Komorbiditätenunclassified
“…Hierbei ist besonders brisant, dass HIV-positive Patienten diese altersassoziierten, also "normalen" Alterserkrankungen zwischen 5 und 10 Jahre früher bekommen als eine alters-und geschlechtsgematchte Vergleichsgruppe aus der Allgemeinbevölkerung [66]. Auch wenn man Rauchen, Substanzgebrauch und andere "Life-style"-bedingte Risikofaktoren aus diesem Vergleich herausnimmt, haben HIV-positive Patienten ein deutlich erhöhtes Risiko früher einen Herzinfarkt oder Schlaganfall zu erleiden als ihre HIV-negativen Altersgenossen [66]. Eine aktuelle Metaanalyse über 5 Studien mit insgesamt 89 713 Teilnehmern zeigte, dass innerhalb von 5 Jahren Follow-up 1245 ischämische Schlaganfälle bei im Durchschnitt 46(46 -50)-jähri-gen, überwiegend (70 %) männlichen Patienten auftraten [67].…”
Section: Bedeutung Von Komorbiditätenunclassified